Evaluating the predictive power of circulating tumor cells for the prognosis of transarterial chemoembolization treatment on patients with advanced hepatocellular carcinoma. Issue 1 (8th January 2021) - Deng, Jun; Chen, Wei; Wu, Xiaoxia; Zhou, Yan; Li, Jun
Abstract : Abstract: Explore the predictive power of Circulating Tumor Cells (CTCs) for evaluating the prognosis of transarterial chemoembolization (TACE) treatment on advanced hepatocellular carcinoma (HCC) patients, and use it to construct a prediction model. We retrospectively analyzed 43 patients with Barcelona Clinic Liver Cancer stage C HCC who underwent TACE treatment. The survival time of 43 advanced HCC patients were 2 to 60 months, with the median survival time of 12 months, 1-, 3-, and 5-year survival rates were 42.9%, 9.0%, and 3.6%, respectively. The OS of patients with high level of CTCs before TACE (CTC1 > 2) was significantly lower than that of patients with low level of CTCs (8 vs 12 months, P  = .040), but there was no significant difference in PFS between the 2 groups ( P  = .926). Meanwhile, there was no significant difference in OS and PFS between patients with high level CTCs and those with low level CTCs at 1 week and 4 weeks after TACE ( P all > .05). In univariate and multivariate Cox regression analysis, the number of lesions and CTC before TACE were the independent influencing factors for prognosis in these patients, and the HR was 3.01 and 1.20, respectively (all P  < .05). The area under curve of COX regression model to predict OS increased with the increase of follow-up time, ranging from 0.56 to 0.85. The CTCs number before TACE is an effective biomarker for predicting the OS of advanced HCC patients. The joint prediction model based on CTCs and tumor number can effectively predict the prognosis of patients with advanced HCC.